Optimalisasi Study Visit Dalam Meningkatkan Mindset Kewirausahaan Di Era Digital Pada Mahasiswa Institut Teknologi Sosial Dan Kesehatan Muhammadiyah Selong - Nur Fitri Eka Asbarini; Abdul Chalel Rahman (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Entrepreneurship in the digital era has become a fundamental cornerstone in facing rapid global changes. The purpose of this study visit program is to fortify students' mindsets in cultivating an entrepreneurial spirit. Moreover, this program prepares the emerging young generation to be self-reliant, possessing the mental readiness and cognitive framework necessary to skillfully merge entrepreneurial competencies with technology insights in the digital age. Research outcomes indicate that through the study visit program, students can broaden their perspectives on entrepreneurship in the digital era. Additionally, from these activities, students can correlate theoretical concepts with real-world practices in the realm of digital business, thereby enabling educational institutions to enhance their graduates into relevant entrepreneurs aligned with the demands of the time.